2018
DOI: 10.1590/s0100-83582018360100045
|View full text |Cite
|
Sign up to set email alerts
|

Interference Periods in Soybean Crop as Affected by Emergence Times of Weeds

Abstract: -Weeds emergence times modify competition with crops. Thus, the hypothesis was that the increase in weed emergence flow decreases the period prior to interference (PPI) in soybeans and increases the critical period of interference prevention (CPIP). The objective was to determine the PPI and the CPIP of weeds in soybean crops as affected by the preferred time of weeds emergence flow. Three experiments were conducted in the field in a randomized block design with four replications. The treatments were arranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…Fomesafen also increased RDM, since its value was 16.9% higher than the one of the control. Increase in HEI and crop biomass ensures better establishment and competitive skills with weeds for environmental resources (Zandoná et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Fomesafen also increased RDM, since its value was 16.9% higher than the one of the control. Increase in HEI and crop biomass ensures better establishment and competitive skills with weeds for environmental resources (Zandoná et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The application of pre-emergent herbicides within the resistance scenario is important to ensure the crop emergence in areas free from competition. Thus, a recent study showed that the emergence time of weeds has a distinct interference capacity in the soybean, with a critical control period ranging from 14 to 48 days after the crop emergence (Zandoná et al, 2018). On the other hand, cover plants reduced the height plants and promoting a better control efficiency.…”
Section: /8mentioning
confidence: 99%
“…The yield results demonstrated that poaceous weed infestation of the soybean crop prompted a 2064 kg ha -1 decline in seeds compared to the weed-free control (Figure 5). The weed interference in soybean during all the crop cycle reduces yield 73 to 94% in different sowing times (Zandona, et al, 2018). Considering a 5% tolerable yield decline, the soybean crop was negatively affected by weed infestation starting at 25 DAE (PAI) (Benedetti et al, 2009).…”
Section: Soybean Yieldmentioning
confidence: 99%
“…Competition of weeds with crops can generate irreversible losses, with no recovery of development or yield, even after the elimination of it (Agostinetto et al, 2014). Moreover, increase in the period when the crop remains with weed interference, greater the damage (Zandona et al, 2018).…”
Section: Soybean Yieldmentioning
confidence: 99%